Comparative Study of Electrocardiographic and Echocardiographic Evidence of Left Ventricular Hypertrophy in Post COVID Hypertensive patients - Dr. Aditya Patidar; Dr. Aditya Patidar; Dr. Asrar Ahmed; Dr. Rajendra Dhar, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: COVID-19 has harmed cardiovascular health, especially hypertensives. Left ventricular hypertrophy (LVH) by chronic hypertension raises cardiovascular risk. Aim: To compare ECG LVH criteria for diagnosing LVH in post-COVID hypertensive patients using ECHO as the gold standard. Materials and Methods: This 12-month observational comparison was done in NIMS Jaipur's General Medicine Department. Written informed consent was obtained from all 80 purposive sampled participants. Left ventricular hypertrophy (LVH) was diagnosed using the Sokolow-Lyon Index and Cornell Voltage Criteria on ECG and ECHO. Age, sex, residence, family history of hypertension, and duration of hypertension for known patients were obtained using a pre-designed questionnaire. Echocardiography verified LVH after ECG. Materials: Our study comprised 80 hypertensives, 52.5% of whom were men. The average age was 56.36 ± 12.35 years, and the average duration of hypertension was 4.57 ± 4.75 years. The average pulse rate was 78 ± 9.46 beats/minute, with systolic and diastolic blood pressures of 135 ± 17.46 and 86 ± 11.43 mmHg, respectively 7.5% had newly diagnosed hypertension, 42.4% family history. Using Sokolow-Lyon criteria, ECG sensitivity and specificity for LVH diagnosis were 46.6% and 98.6%, with a PPV of 96.4% and an NPV of 70.5%. Cornell Voltage criterion yielded 40.1% sensitivity, 94.9% specificity, 86.0% PPV, and 67.3% NPV. Using both ECG criteria increased sensitivity to 53.0%, specificity to 94.9%, PPV to 87.9%, and NPV to 76.0%. Conclusion: Cornell Voltage criteria had 40.1% ECG sensitivity for left ventricular hypertrophy (LVH) and Sokolow-Lyon criteria 46.6%. Using both criterion increases sensitivity to 53.0%. High specificity (>95%) for both criteria. Due to its low sensitivity, ECG cannot screen post-COVID hypertensives for LVH.